Impact of COVID-19 program adaptations on costs and cost-effectiveness of community management of acute malnutrition program in South Sudan - Kemish Kenneth Alier; Hannah Tappis; Sule Ismail; Shannon Doocy (Cambridge University Press, 2024)
Abstract Objective: We assessed the impact of the COVID-19 pandemic and the protocol adaptations on cost and cost-effectiveness of community management of acute malnutrition (CMAM) program in South Sudan. Design: Retrospective program expenditure-based analysis of non-governmental organisation (NGO) CMAM programs for COVID-19 period (April 2020-December 2021) in respect to pre-COVID period (January 2019-March 2020). Setting: Study was conducted as part of a bigger evaluation study in South Sudan. Participants: International and national NGOs operating CMAM programs under the nutrition cluster participated in the study. Results: The average cost per child recovered from the programme declined by 20 % during COVID from $133 (range: $34-1174) pre-COVID to $107 (range: $20-333) during COVID. The cost per child recovered was negatively correlated with programme size (pre-COVID r-squared = 0·58; during COIVD r-squared = 0·50). Programmes with higher enrollment were cheaper compared with those with low enrolment. Salaries, ready to use food and community activities accounted for over two-thirds of the cost per recovery during both pre-COVID (69 %) and COVID (79 %) periods. While cost per child recovered decreased during COVID period, it did not negatively impact on the programme outcome. Enrolment increased by an average of 19·8 % and recovery rate by 4·6 % during COVID period. Conclusions: Costs reduced with no apparent negative implication on recovery rates after implementing the COVID CMAM protocol adaptations with a strong negative correlation between cost and programme size. This suggests that investing in capacity, screening and referral at existing CMAM sites to enable expansion of caseload maybe a preferable strategy to increasing the number of CMAM sites in South Sudan.